SQL WEBSITE-BASED LIBRARY INFORMATION SYSTEM DESIGN OF SMKN8 BANDUNG - Rian Pirnandi Turnip; Ari Purno Wahyu Wibowo (Jurnal Darma Agung, 2022)
Data collection is generally done manually, but this manual method has Page 01-13 drawbacks, namely data collection becomes ineffective, not neatly arranged, and searching for data takes a lot of time. Likewise with library management at SMKN 8 Bandung, data collection is still manual so that there are often many errors for that it is necessary to have a web-based library information system where data management will be more organized and according to the wishes of the user. The research method used is research and development with the sql website development method. The data collection methods used were interviews and observations. The interview method is used to determine user needs, while the observation is for testing aspects of performance efficiency. The results of this study are (1) the system is proven that the level of feasibility of a web-based library information system using PHP and a MYSQL database server. (2) The test results prove that the level of feasibility of a web-based library information system in the usability aspect of the small group is 84.22% with very decent criteria and 91.2% large group with very feasible criteria, and the performance efficiency aspect is 98.64 with grade A.